Differentially expressed genes in potato sprouts after potassium phosphite application - Feldman, M. (2009)
We are studying the role of phosphites in disease control management, yield and potato tuber quality. In brief, our previous results showed a number of promising properties associated with these compounds. When we applied potassium phosphites (KPhi) at 3 litre $latex ha^{-1} $ to seed tubers immediately after cutting, this promoted early emergence, an increased in stem number and diameter, early tuber initiation and an increased in the number of tubers per plant. In addition to these physiological effects, phosphite treatment also resulted in greater resistance in seed tubers to Phytophthora infestans, Fusarium solani and Rhizoctonia solani. In order to understand the mechanisms which regulate these responses, we analyzed the changes in gene expression in tubers seeds at early stage of sprouting after KPhi treatment. Preliminary results of microarray analysis from potato sprouts treated or not with KPhi, showed that 26 genes were upregulated in the treated ones. These genes were classified into 5 groups: plant defense, metabolism, abiotic stress, transcription factors and unknown genes. We performed semiquantitative RT-PCR assays of some of these genes to validate the results. Interestingly one of these genes was CULLIN 1, involved in jasmonic acid mediated signaling pathway. This result may support the hypothesis that phophites could be involved in triggering IR (induced resistant).